2010
DOI: 10.1108/17471111011083455
|View full text |Cite
|
Sign up to set email alerts
|

Linking strategic logistics change to labor rights

Abstract: PurposeThis paper aims to describe how research literature and logistics practitioners respectively describe the link between logistics and corporate social responsibility, focusing on the link between strategic logistics change (location, capacity and number of facilities as well as the design of supplier and customer network) and labor rights.Design/methodology/approachA literature review on the topics corporate social responsibility, green logistics and sustainable supply chain management was performed. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The explorative study by Murphy and Poist (2002) showed that safe movement and storage of goods, as well as employee health and safety are of great importance to practitioners. Other social aspects of CSR discussed in the logistics literature include workforce diversity (Andre, 1995, Lynagh et al, 1999, job satisfaction and working conditions (Min and Lambert, 2002), ethics (Razzaque and Hwee, 2002, Maloni and Brown, 2006, Pretious and Love, 2006, Miao et al, 2012, and human and labour rights (Björklund, 2010). Perry and Towers (2013) present a discussion of a wide range of social aspects of CSR in their attempt to develop a framework for CSR implementation in fashion supply chains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The explorative study by Murphy and Poist (2002) showed that safe movement and storage of goods, as well as employee health and safety are of great importance to practitioners. Other social aspects of CSR discussed in the logistics literature include workforce diversity (Andre, 1995, Lynagh et al, 1999, job satisfaction and working conditions (Min and Lambert, 2002), ethics (Razzaque and Hwee, 2002, Maloni and Brown, 2006, Pretious and Love, 2006, Miao et al, 2012, and human and labour rights (Björklund, 2010). Perry and Towers (2013) present a discussion of a wide range of social aspects of CSR in their attempt to develop a framework for CSR implementation in fashion supply chains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Figure 2,3 5, 6, 10 and 17 responses influence the consumer boycott behavior. C: According to Björklund (2010), if firms start taking labor/employee rights-focused, socially responsible supply chain decisions, in scenarios like vendor selection, the understanding of the importance of labor rights can be improved and soon persistent issue that linger in spite of legal challenges can be tackled. Figure 3 and 4 demonstrates that while most employees strongly agree on the importance of this as a social issue, their confidence on engagement from the firm is rather limited.…”
Section: Resultsmentioning
confidence: 99%
“…Of the many issues, Table 1 identifies those of the highest impact reviews, and each is briefly described. Björklund, 2010;Markley & Davis, 2007;Ansett, 2007D Employment Discrimination Roscigno, 2019E Ethics Morais, 2017Ellis & Higgins, 2006;Kolk andVan Tuldere, 2002 F Fair trade andtransparency Olorunniwo &Peters et al, 2011G Gender Morais, 2017Mani et al, 2015;Yawar andSeuring, 2017 H Health, safety andwellbeing Mani et al, 2015;Markley & Davis, 2007;Morais, 2017;Yawar and Seuring, 2017;Closs et al, 2011;Pullman et al, 2009I Housing Mani et al, 2015Read et al, 2012 J Human rights violation Yawar andSeuring, 2017;Klassen and Vereecke, 2012;Mani et al, 2015;Morais, 2017 K Labor conditions Klassen andVereecke, 2012;Yawar and Seuring, 2017;Ageron et al, 2012;Leire and Mont, 2009;Smith, 2007;Matos & Hall, 2007L Local community empowerment Simões, 2014Morais, 2017 Mani et al, 2015;Kumar and Rahman, 2015;Yawar and Seuring, 2017;Hall, 2007 Z Work-life balance Kumar and…”
Section: Social Issues In Supply Chain (Sc)mentioning
confidence: 99%
“…The discourse can be traced back to the 1950s (Carroll, ), although its appearance in SCM is more recent (e.g., Andersen & Skjoett‐Larsen, ; Carter, , ; Carter & Jennings, , , ; Jørgensen, Pruzan‐Jørgensen, Jungk & Cramer, ; Maloni & Brown, ; Park‐Poaps & Rees, ; Phillips & Caldwell, ). However, the implementation of CSR practices remains limited in SCM (see Björklund, ) and, unlike lean, there is little evidence of a dominant discourse that has been translated into institutionalized SCM practices.From a discourse‐analytic perspective, we can see that the limited application of CSR in SCM results from a discursive struggle among businesses, academics, and nongovernmental organizations (NGOs) concerning what CSR means. Many academics and NGOs call for a strong form of CSR premised on the idea that many production, consumption, and employment practices used in business are unethical and unsustainable.…”
Section: Discourse and Discourse Analysismentioning
confidence: 99%